What is the Value of Youth Social Care in the Covid-19 Pandemic?: Lessons from the Loloan Youth Movement in Jembrana Bali - Sabarudin (Proceeding International Conference on Religion, Science and Education, 2022)
The purpose of this paper is to critically describe and analyze the social role of youth in loloan villages who are members of the Loloan Youth Movement both before and during the pandemic. These social roles are critically and fundamentally studied, especially the values that encourage Loloan youth to move together to advance their territory. Qualitative research with the sociological approach of education takes place in the Loloan area of Jembrana subdistrict of Jembrana district of Bali province. The object of the study is the social activity of the Loloan Youth Movement. The study subjects were taken using purposive sampling. Data collection uses interviews, observations, and documentation studies, with validity tests using triangulation techniques and sources. The results showed, first, the Loloan Youth Movement stood because of the desire to bring loloan youth towards activities that benefit the community. Second, social activities carried out by the Loloan Youth Movement both before and during the covid-19 pandemic period include: fundraising through charity piggy banks, then channeled in the form of social funds for education, health, poor families, and compensation for orphans. Third, the youths in Loloan District Jembrana actively conduct social activities, both before and during the covid-19 outbreak, The historical background of Loloan as a base of Bugis-Malay ethnic who has noble tradition values wants to be resurrected, to show the majority Hindu Balinese community, that Loloan youth have high social concern for others, regardless of religion. The study contributes to literature in the domains of social movements, cultural movements, and educational sociology, by describing the strategies and challenges faced by youth movers and describing the strategies used by them in moving youth.